The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.48550/arxiv.2208.04167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unconventional Berezinskii-Kosterlitz-Thouless Transition in the Multicomponent Polariton System

Abstract: We study a four-component polariton system in the optical parametric oscillator regime consisting of exciton/photon and signal/idler modes across the Berezinskii-Kosterlitz-Thouless (BKT) transition. We show that all four components share the same BKT critical point, and algebraic decay of spatial coherence with the same critical exponent. However, while the collective excitations in different components are strongly locked, both close to and far from criticality, the spontaneous creation of topological defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…( 26) together with Eqs. ( 17), ( 20), (21), and ( 23)- (25), can be considered as a function of three independent parameters: γ/g, κ and ǫ + /ǫ − . In Fig.…”
Section: B Bogoliubov Theory With Nonlinear Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 26) together with Eqs. ( 17), ( 20), (21), and ( 23)- (25), can be considered as a function of three independent parameters: γ/g, κ and ǫ + /ǫ − . In Fig.…”
Section: B Bogoliubov Theory With Nonlinear Correctionmentioning
confidence: 99%
“…In two dimensions, the KPZ phase dynamics was predicted to make long range phase coherence impossible in isotropic systems [13,17]. Numerical studies on the other hand have shown a transition toward a state with algebraic decay of the coherence [18] and an associated disappearance of vortex-antivortex pairs [18][19][20][21] without the formation of topological defects even when the spatiotemporal correlations feature KPZ scaling [22,23]. Since computational resources limit the system sizes for numerical studies, the discrepancy between the renormalisation group studies could be due to finite size effects, but at present it does not seem that the issue is fully settled.…”
Section: Introductionmentioning
confidence: 99%